2016
DOI: 10.1098/rsfs.2016.0055
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the preparation and application of multifunctional iron oxide and liposome-based nanosystems for multimodal diagnosis and therapy

Abstract: Nowadays, thanks to the successful discoveries in the biomedical field achieved in the last two decades, a deeper understanding about the complexity of mechanistic aspects of different pathological processes has been obtained. As a consequence, even the standard therapeutic protocols have undergone a vast redesign. In fact, the awareness about the necessity to progress towards a combined multitherapy in order to potentially increase the final healing chances has become a reality. One of the crucial elements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 134 publications
0
22
0
Order By: Relevance
“…Despite its promising potential, even the organotin-based drugs present some limitations that make mandatory the use of a proper vector for their biomedical application. In this sense, nanomaterials can act as suitable vectors for metallodrug delivery by (i) protecting the active species from degradation, (ii) enhancing their therapeutic activity [26], (iii) increasing drug bioavailability and specificity, or (iv) increasing the solubility [23,[27][28][29][30]. Because of its synthetic flexibility and biocompatibility, mesoporous silica-based nanostructured materials (MSN) represent one of the most used nanovectors in biomedicine, with special importance in metallodrug-based drug delivery systems [23,[31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its promising potential, even the organotin-based drugs present some limitations that make mandatory the use of a proper vector for their biomedical application. In this sense, nanomaterials can act as suitable vectors for metallodrug delivery by (i) protecting the active species from degradation, (ii) enhancing their therapeutic activity [26], (iii) increasing drug bioavailability and specificity, or (iv) increasing the solubility [23,[27][28][29][30]. Because of its synthetic flexibility and biocompatibility, mesoporous silica-based nanostructured materials (MSN) represent one of the most used nanovectors in biomedicine, with special importance in metallodrug-based drug delivery systems [23,[31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in this last research area, MSN have shown a lots of benefits [46] such as a variable and controllable particle and pore size, a large surface area that can be selectively functionalized for drug delivery or high biocompatibility [47][48][49] or the possibility of combining several functionalities in a single nanosystem [50]. In this sense, one of these possible combinations is represented by the theranosis or the generation of a single nanoentity able to combine therapeutic and diagnostic features at the same time [28,[51][52][53][54][55]. In general, nanovectors may deliver their therapeutic cargo via two possible pathways: enhanced permeability and retention (EPR) effect [56] or receptor-mediated transcytosis [57].…”
Section: Introductionmentioning
confidence: 99%
“…To compensate the above described drawbacks, among all non-invasive clinical imaging modalities, Magnetic Resonance Imaging (MRI) results as the most attractive one because of its lack of radiation, its ability to facilitate deep tissue penetration and, mainly, to provide high spatial resolution. 22,30,31 Consequently, based on the considerations made above, we planned joining these three imaging modalities -CT, MRI and OI-thus developing a finely designed complementary molecular imaging agent with high spatial resolution, high sensitivity, deep tissue penetration and easy operational features (e.g. no radioactive nuclei application such as in positron emission tomography (PET) imaging).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…[16][17][18][19] Due to its intrinsic physic characteristics, each individual imaging modality can provide only limited information in terms of spatial and temporal resolution, sensitivity and penetration depth, being unable promoting an accurate imaging diagnosis by itself individually. [20][21][22] In other terms, no single molecular imaging technique is able to provide a 'perfect' diagnosis. Consequently, the multimodal molecular imaging concept (combination of different imaging techniques) has rapidly become the reference strategy to bypass the intrinsic limitations of each individual imaging modality while maximizing its advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide nanoparticles (IONPs) have been broadly used as imaging probes [82]. Their sizedependent MRI properties together with their superparamagnetic behavior, biocompatibility and chemical stability place them as a particularly important NP type for biomedical applications [83].…”
Section: Iron Oxide Nanoparticles (Ionps)mentioning
confidence: 99%